2020
DOI: 10.1002/ijgo.13393
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of uterine tamponade devices for the treatment of postpartum hemorrhage: A systematic review

Abstract: Background: Uterine tamponade is widely promoted for treating refractory postpartum hemorrhage (PPH); however, its cost-effectiveness may vary depending on unit costs and setting. Objective: To review available data on cost-effectiveness of uterine tamponade devices when used for PPH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Many researchers have developed PPH care bundles, but there has been limited evidence to demonstrate which, if any, bundles lead to improved outcomes. Vogel et al conducted a systematic review to identify which care bundles were safe and effective for the prevention and treatment of PPH 6 . They registered their protocol with the International Prospective Register of Systematic Reviews and followed the Preferred Reporting Items of Systematic Reviews and Meta‐Analyses guidance for reviews of complex interventions.…”
Section: Are Care Bundles the Solution To The Diagnosis And Managemen...mentioning
confidence: 99%
“…Many researchers have developed PPH care bundles, but there has been limited evidence to demonstrate which, if any, bundles lead to improved outcomes. Vogel et al conducted a systematic review to identify which care bundles were safe and effective for the prevention and treatment of PPH 6 . They registered their protocol with the International Prospective Register of Systematic Reviews and followed the Preferred Reporting Items of Systematic Reviews and Meta‐Analyses guidance for reviews of complex interventions.…”
Section: Are Care Bundles the Solution To The Diagnosis And Managemen...mentioning
confidence: 99%
“…An example is uterine balloon tamponade, which was made available globally in a short period of time, because balloons could be easily made from a condom and a catheter, as opposed to the time-consuming processes of registration and distribution of purpose-designed devices. The cost of uterine tamponade devices ranges from USD 0.64 to USD 400 [ 35 ].…”
Section: Novel Approaches To Uterine Balloon Tamponadementioning
confidence: 99%
“…Comparison with other reviews of economic evaluations in maternal health similarly found that research in this area has increased. Previous reviews typically had a narrower focus, including studies focused on a single or specific set of interventions or evidence from specific settings [9][10][11][12][13][14] , and consequently identified a smaller number of eligible studies (typically less than 30). For example, a 2018 systematic review of health systems strengthening economic evaluations in maternal and perinatal health identified 24 eligible studies, 23 of which were published since 2000 13 .…”
Section: Key Findings and Interpretationmentioning
confidence: 99%
“…The 2016 Disease Control Priorities summarised cost-effectiveness evidence for selected, high-value maternal interventions, identifying 26 studies 10 . More recently, systematic reviews of economic evaluations have been conducted for single interventions as part of WHO recommendation updates 11,12 . Other reviews have focused on economic evaluations of certain categories of interventions in LMICs, such as health systems strengthening strategies, or programs to increase utilisation and provision of care 13,14 .…”
Section: Introductionmentioning
confidence: 99%